O processo eleitoral brasileiro de 2018 sob um olhar da análise de discurso: entre a prisão de Lula e o atentado a Bolsonaro, legitimidade e democracia em disputa na imprensa - Jesus, Gilvan Santana de (2022)
The main objective of this doctoral thesis is to understand how the 2018 presidential elections in Brazil are signified in/by the press. For this, the research takes as a theoreticalmethodological contribution the Discourse Analysis of French tradition, more specifically, of a materialist basis, which has Michel Pêcheux as a precursor. Our interpretation gestures particularize this electoral process from the analysis of 40 covers of different journalistic vehicles, circulating in the digital/virtual space, regarding two important and decisive events of the pre-electoral political situation, namely: a) the prison of ex-president Luiz Inácio Lula da Silva (PT), which took place on April 7, 2018; b) and the attack on the candidate for the presidency of the Republic, Jair Messias Bolsonaro (at that time, affiliated with the PSL), which took place on September 6 of the same year. The meanings that are in circulation in this period, after all, will produce discursive resonances (SERANI, 1993) in the way in which the journalistic media will reflect matters concerning the elections. The work is structured in four chapters, one methodological, one theoretical and two analytical, respectively: I. “Building the method in Discourse Analysis: on the disjunctive logic that crosses the electoral process”; II. “Theoretical device of Discourse Analysis: the other's place in the constitution of the subject”; III. “Lula's prison as a discursive event: effects of the sense of fulfillment of democracy”; IV. “The attack on Bolsonaro as a discursive event: meaning effects of the rupture of democracy”. This comparative movement of analysis between the two events mentioned made it possible for us to observe a scenario strongly taken by bilateral antagonism, a phenomenon that, in Brazil, has been constituting itself for some time as an evident meaning and that erases another possibility for the voters to vote. In this way, we can see how the meaning effects of “bipolarization” and a “disjunctive logic” (PÊCHEUX, 2015) affect the construction of the electoral process in the journalistic media. In addition, we also verified how the meanings of democracy are, recurrently, in dispute: on the one hand, Lula's imprisonment is meant as the legitimate and democratic path to be followed, therefore, as the expected outcome; on the other hand, the attack on Bolsonaro constitutes an undemocratic event, which not only produces a rupture with the democratic ideals of the country but also sensitizes the reader/elector about this attack, in view of the “spectacularization” that constitutes it. (GREGOLIN, 2003). In this perspective, we defend the thesis that the election of Jair Bolsonaro is being constructed, discursively, in the press, under the eyes of the reader/elector, as a legitimate and democratic path, considering the functioning of effects of meanings of pre-constructed constitutive of Brazilian democracy, which is operating in our discursive corpus. With the development of this research, we provide means for a better understanding of the current political-electoral scenario in Brazil, observing how the discursive memory is updated, always in the tension between something that repeats and structures the electoral process and something that breaks, slips and escapes the domain of the subject (PÊCHEUX, 2015; ORLANDI, 2015).